Complex, Intelligent, and Software Intensive Systems Proceedings of the 12th International Conference on Complex, Intelligent, and Software Intensive Systems (CISIS-2018) - Barolli, Leonard; Javaid, Nadeem; Ikeda, Makoto; Takizawa, Makoto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a platform of scientific interaction between the three challenging and closely linked areas of ICT-enabled-application research and development: software intensive systems, complex systems and intelligent systems. Software intensive systems strongly interact with other systems, sensors, actuators, devices, other software systems and users. More and more domains are using software intensive systems, e.g. automotive and telecommunication systems, embedded systems in general, industrial automation systems and business applications. Moreover, web services offer a new platform for enabling software intensive systems. Complex systems research is focused on the overall understanding of systems rather than their components. Complex systems are characterized by the changing environments in which they interact. They evolve and adapt through internal and external dynamic interactions. The development of intelligent systems and agents, which are increasingly characterized by their use of ontologies and their logical foundations, offer impulses for both software intensive systems and complex systems. Recent research in the field of intelligent systems, robotics, neuroscience, artificial intelligence, and cognitive sciences are vital for the future development and innovation of software intensive and complex systems.
Home Energy Management using Optimization Techniques -- Hybrid Bacterial Foraging Tabu Search Energy Optimization Technique in Smart Homes -- A Hybrid Tabu-Enhanced Differential Evolution Meta-heuristic Optimization Technique for Demand Side Management in Smart Grid -- Performance Evaluation of WMN-PSOSA Considering Exponential and Weibull Distributions -- CRRP Analysis of Cloud Computing in Smart Grid -- Evaluation of a Protocol to Prevent Malicious Information Flow in P2PPS Systems -- A Fuzzy-based Plant Cultivation Support System -- Performance of WRF Cloud Resolving Simulations with Data Assimilation on Public Cloud and HPC Environments -- Personalized Group Recommendation Model based on Argumentation Topic -- Application of Bird Swarm Algorithm for Solution of Optimal Power Flow Problems.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence